The importance of mathematics in computer science / Z. Abal Abas and A.F.N. Abd Rahman - Abal Abas, Z.; Abd Rahman, A.F.N. (2006)
This report will analyze the performance of 220 first year ICT undergraduate in KUTKM in two subjects that are offered concurrently in order to test the initial hypotheses which stated that those who are doing well in mathematical subject are believed to do well also in computer science area especially in programming. Thus, two subjects namely BACS 1253 - Mathematic for Computer Science 1 and BITP 1113- Programming Techniques were chosen and the student's marks for the final examination and the total marks for each of them are gathered and analyzed by using SPSs. Pearson correlation is chosen since the data gained is quantitative and normally distributed with linear relationship according to the scatter plot graph. The result obtained from this report will be then used to highlight the significance of mathematical foundation in any computer science curriculum.